Muscle strength and anaerobic performance in football players with cerebral palsy. Issue 2 (April 2016) - Yanci, Javier; Castagna, Carlo; Los Arcos, Asier; Santalla, Alfredo; Grande, Ignacio; Figueroa, Joaquín; Camara, Jesús
Abstract: Background: This is the first study that quantified the anaerobic performance in football players with cerebral palsy (CP). Objective: This study aimed to examine anaerobic fitness in a population of football players with CP using vertical jumping (VJ) and Wingate tests. Methods: Twelve players (age 26.8 ± 4.8 yr, body mass 66.2 ± 4.8 kg, height 173.7 ± 6.4 cm, body mass index 22.2 ± 1.9 kg m −2 ) from the Spanish National Football Team with CP which had 9.4 ± 3.7 years of playing experience performed the VJ and Wingate anaerobic tests. Results: Vertical jump height was 20.0 ± 1.2 cm for squat jump (HSJ) and 23.9 ± 5.4 cm for countermovement jump (HCMJ). Wingate test peak power (PPOW) was 490.6 ± 125.8 W (7.35 ± 1.53 W kg −1 ). HCMJ was largely ( r  = −0.631, p  = 0.028) and very-largely ( r  = −0.710, p  = 0.01) associated with PPOW (W kg −1 ) and mean power output (MPOW) (W kg −1 ), respectively. Squat jump test peak power (W) showed a large association ( r  = −0.656, p  = 0.021) with MPOW (W and W kg −1 ). The CMJ height resulted 19.5% higher than SJ. Conclusions: Results showed low VJ and anaerobic capacity of football players with CP compared to national players without CP and the general population. In football players with CP the difference (19.5%) between VJ with or without countermovement (CMJ-SJ) was higher than reported for national players without CP. Further studies examining the effect of football practice on neuromuscular performance in subjects with CP are warranted.